Thioredoxin-1 decreases alpha-synuclein induced by MPTP through promoting autophagy-lysosome pathway - Rou Gu; Liping Bai; Fang Yan; Se Zhang; Xianwen Zhang; Ruhua Deng; Xiansi Zeng; Bo Sun; Xiaomei Hu; Ye Li; Jie Bai (Cell Death Discovery, 2024)
Abstract Parkinson’s disease (PD) is characterized by the formation of Lewy body in dopaminergic neurons in the substantia nigra pars compacta (SNpc). Alpha-synuclein (α-syn) is a major component of Lewy body. Autophagy eliminates damaged organelles and abnormal aggregated proteins. Thioredoxin-1 (Trx-1) is a redox regulating protein and plays roles in protecting dopaminergic neurons against neurotoxicity induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). However, the relationship between Trx-1 and α-syn in PD is still unknown. In the present study, the movement disorder and dopaminergic neurotoxicity in MPTP-treated mice were improved by Trx-1 overexpression and were aggravated by Trx-1 knockdown in the SNpc in mice. The expression of α-syn was increased in the SNpc of MPTP-treated mice, which was inhibited by Trx-1 overexpression and was exacerbated in Trx-1 knockdown mice. Autophagosomes was increased under electron microscope after MPTP treatment, which were recovered in Trx-1 overexpressing mice and were further increased in Trx-1 knockdown in the SNpc in mice. The expressions of phosphatase and tensin homolog deleted on chromosome ten (PTEN)-induced putative kinase 1 (PINK1), Parkin, LC3 II and p62 were increased by MPTP, which were blocked in Trx-1 overexpressing mice and were further increased in Trx-1 knockdown mice. Cathepsin D was decreased by MPTP, which was restored in Trx-1 overexpressing mice and was further decreased in Trx-1 knockdown mice. The mRFP-GFP-LC3 green fluorescent dots were increased by 1-methyl-4-phenylpyridinium (MPP+) and further increased in Trx-1 siRNA transfected PC12 cells, while mRFP-GFP-LC3 red fluorescent dots were increased in Trx-1 overexpressing cells. These results indicate that Trx-1 may eliminate α-syn in PD mice through potentiating autophagy-lysosome pathway.